2011
DOI: 10.1590/s0037-86822011000800010
|View full text |Cite
|
Sign up to set email alerts
|

O controle da transmissão transfusional

Abstract: A alta prevalência de doadores chagásicos nos bancos de sangue do Brasil (6,9%) e da América Latina (6,5%), nas décadas de 60 e 70, aliada ao combate ao vetor a partir dos anos setenta, fez com que a doença de Chagas transfusional, a partir da década de oitenta, se tornasse o principal mecanismo de transmissão da doença na maioria dos países endêmicos. Contudo, os resultados altamente favoráveis do combate ao vetor e da cobertura sorológica dos doadores, reduziu a prevalência de soropositividade para 0,2% e 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
10

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 18 publications
1
16
0
10
Order By: Relevance
“…In Brazil in the 1950s, the estimated average prevalence of positive serology for T. cruzi among potential blood donors was 8.3%. This decreased to 6.9% in the 1960s and 1970s, dropping to 3.2% in the late 1980s and early 1990s (96) . A Health ministry report from January to June 1994 stated an estimated prevalence of Chagas disease through blood transfusion, by the public blood donation network to different geographic regions nd Brazilian Consensus on Chagas Disease, 2015 of the country, of 0.75% (95) .…”
Section: Transmission By Blood Transfusion and Transplantation Of Tismentioning
confidence: 88%
See 2 more Smart Citations
“…In Brazil in the 1950s, the estimated average prevalence of positive serology for T. cruzi among potential blood donors was 8.3%. This decreased to 6.9% in the 1960s and 1970s, dropping to 3.2% in the late 1980s and early 1990s (96) . A Health ministry report from January to June 1994 stated an estimated prevalence of Chagas disease through blood transfusion, by the public blood donation network to different geographic regions nd Brazilian Consensus on Chagas Disease, 2015 of the country, of 0.75% (95) .…”
Section: Transmission By Blood Transfusion and Transplantation Of Tismentioning
confidence: 88%
“…The risk of transmission by blood transfusion is dependent on various factors: I) the presence of the parasite in the blood or blood component transfused; II) type and number of infected blood products transfused; III) immune status of the recipient; IV) quality of the clinical-epidemiological screening; V) level of coverage of the serologic screening of donors; and VI) sensitivity of serologic tests used to screen blood donation candidates (4) (23) (95) (96) .…”
Section: Transmission By Blood Transfusion and Transplantation Of Tismentioning
confidence: 99%
See 1 more Smart Citation
“…With step-by-step control of natural transmission, particularly by means of eradication of the vector in various endemic countries, blood transfusions became the main mechanism of dissemination of Chagas disease in these countries during the 80s and the 90s 5 . The possibility of transmission of this disease by means of blood transfusion was rumored in 1936 in Argentina 6 and confirmed in 1952 in Brazil 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In an analysis of 25,207 blood donations performed in the Hematology Unit of Hospital Universitário de Santa Maria, southern Brazil, from January 2004 to December 2007, Cogo et al 9 found that 246 (0.98%) donors presented a positive or indeterminate serology for Chagas disease. The prevalence of positive serology for Chagas disease may be explained by the higher number of individuals who had not sought other health care services yet and whose disease had not been detected before, since it is usually asymptomatic, by the high rate of migration from rural to urban areas, and by improvements in housing, educational, and health conditions 34,35 . Serological screening for hepatitis C is performed by two tests: detection of anti-HCV antibodies or combined detection of anti-HCV antibodies and HCV antigens; and detection of HCV nucleic acid 1 .…”
mentioning
confidence: 99%